RESPONSE OF Solanum melongena L. SEEDLINGS GROWN UNDER SALINE CALCAREOUS SOIL CONDITIONS TO A NEW ORGANO-MINERAL FERTILIZER - W. M. Semida; T. A. Abd El-Mageed; S. M. Howladar; G. F. Mohamed; M. M. Rady (Journal of Animal and Plant Sciences, 2015)
This study was planned to investigate the effect of soil application with an organo-mineral fertilizer [OMF; a 5:2:1 (w/w/w) mixture of green waste compost, elemental sulphur (S) and humic acid (HA), respectively] on physical and chemical characteristics of a reclaimed saline calcareous soil (ECe = 6.47 dS m−1 and CaCO3 = 15.63%). In addition, growth, physiological and anatomical characters of eggplant (Solanum melongena L.) seedlings grown under the tested soil were investigated. The experiments were arranged in a completely randomized design with 4 experimental OMF treatments (i.e., 0, 10, 20, or 30 g kg−1 soil) with 10 replicates. The OMF-treated plants showed increased growth, concentrations of total soluble sugars, free proline, anthocyanin, K and Ca, ratios of Ca:Na and K:Na, and photosynthetic efficiency. An enhanced seedling anatomy was also observed with soil amendment by OMF. On the other hand, the OMF application led to a substantial reduction in soil salinity (ECe) and pH and an increase in field capacity and available water. The tested organo-mineral fertilizer could be recommended as a soil amendment for vegetable crops, including eggplant to overcome the adverse effects of salinity stress in newly-reclaimed soils.
Keywords: Organo-mineral fertilizer; Saline calcareous soil; Eggplant; Photosynthetic apparatus; Soil characteristics